An evaluation of antibacterial potency of royal jelly as an intracanal medicament - Baja Gokulkrishna Koyyur; Shruti Bhandary; Priyanka Sannappa Raju (Conservative Dentistry Journal, 2026)
Background: Enterococcus faecalis is a resistant microorganism commonly associated with persistent root canal infections and endodontic treatment failure. Therefore, effective intracanal medicaments, including natural alternatives such as royal jelly, are being investigated to enhance disinfection. Purpose: This study aimed to evaluate antibacterial efficacy of royal jelly as an intracanal medicament compared with 2% chlorhexidine gel and calcium hydroxide against Enterococcus faecalis. Methods: Fifty-one extracted single-rooted human teeth were decoronated and biomechanically prepared using the ProTaper Universal system up to the F3 file. Following sterilization, root canals were inoculated with Enterococcus faecalis (ATCC 29212) and incubated for 24 h. Specimens were randomly divided into three groups (n = 17): Group 1, royal jelly; Group 2, 2% chlorhexidine gel; and Group 3, calcium hydroxide. Intracanal medicaments were placed for seven days. Dentin samples were collected, cultured on brain–heart infusion agar, and colony-forming units (CFU) were counted to assess bacterial reduction. Statistical analysis was performed using one-way ANOVA or Kruskal–Wallis test, with significance set at p < 0.05. Results: The 2% chlorhexidine gel group showed the greatest reduction in Enterococcus faecalis CFU. Royal jelly demonstrated moderate antibacterial activity, which was significantly superior to that of calcium hydroxide but inferior to that of chlorhexidine. Calcium hydroxide exhibited the lowest antibacterial efficacy. Conclusion: Within the limitations of this in vitro study, 2% chlorhexidine gel was the most effective intracanal medicament against Enterococcus faecalis. Royal jelly showed promising antibacterial activity and may serve as a potential natural alternative, warranting further clinical investigations.